A Semi-Quantitative Assessment of Clay Content in Sedimentary Rocks Using Portable X-Ray Fluorescence Spectrometry - Kessler, L.; Ramasamy, Nagarajan (CAFET-INNOVA Technical Society, Hyderabad, India, 2012)
This paper deals with assessment of clay content in sedimentary rocks using portable X-ray fluorescence spectrometry. Whilst measuring chemical properties of sedimentary rocks, it was noted a positive, quasi-linear correlation between the rock’s Rb concentration and both percentage of clay fraction, and equally gamma ray emission. Rb is relatively easy to measure and provides a semi-quantitative assessment of a sedimentary rock’s clay content. The measurement error of the tool is less than 10 %. Initial data indicate that the measurement is sensitive to clay mineral composition, given some samples deviate from others showing higher or lower-thanexpected values. In clastic sediments, the Rb-XRF method can be used as an alternative to Gamma-Ray in determining clay content, such as to describe the cleanness of sand. Furthermore in carbonate rocks, the XRFmeasurements can be used to fairly accurately determine the content of clay. In such way, industrial carbonate hardrock’s, clay content can be correlated with rock strength. By using XRF, it was demonstrated in the ‘failed’ Kpg.Opak quarry that the clay content some 20 % in the rock matrix. The high clay content is responsible here for areduced industrial quality of the hard rock. With this method, limestone strength can be estimated on the spot. Withproper calibration, the tool might also be used to detect clay mineral composition semi-quantitatively.